Quality of seeds and seedlings of Cedrela fissilis Vell. due to the biometry of berry and seeds in different origins - Pereira, Mariane de Oliveira; Navroski, Marcio Carlos; Hoffmann, Pablo Melo; Grabias, Jeniffer; Blum, Christopher Thomas; Nogueira, Antonio Carlos; Rosa, Diego Pereira (Revista de Ciências Agroveterinárias, 2018)
Cedrela fissilis is a Brazilian native species with outstanding use in the timber sector and in the recovery of degraded areas. There is a need for a better understanding of the differences and genetic gains that may exist in relation to different origins and progenies. The objective of the study was to analyze the biometry of fruits and seeds of Cedrela fissilis as a function of different origins and matrices related to the initial growth of seedlings, besides evaluating the best photoperiod in germination. The seeds were collected in matrices from two sources (Fernandes Pinheiro and Lapa) for biometry and the weight of one thousand seeds per matrix. Seeds of the two provenances were submitted to different photoperiods (12, 16 and 24 hours of white light and 24 hours in the dark), the germination and the germination rate index (ORI) was evaluated. The initial growth of the seedlings was evaluated through the measurement of morphological characteristics after every 30 days. The experiments were performed in a completely randomized design and the data submitted to analysis of variance at the 5% level, the averages being compared by the Tukey test and/or polynomial regression. There were biometric differences between fruits and seeds between the matrices, with no relation to the origin. Regarding the germination rate and ORI among the provenances, Fernandes Pinheiro presented the best results. In relation to the photoperiod, there was no difference in germination in relation to light levels, and the ORI was higher for seeds germinated in the dark. Fernandes Pinheiro obtained higher initial growth of the seedlings in relation to the Lapa origin and this difference increases throughout the evaluations. In general, the experiments showed a difference between the provenances, having a relation with the quality of seeds and seedlings formed.